Compliance: norms as an instrument and a threat to the administration - Sanclemente Arciniegas, Javier (Cuadernos de Administración, 2019)
This document analyzes the legal notion of compliance in relation to the activity of business administration. We will see that this institution expresses itself through a set of norms that guide the performance of companies seeking to mitigate the risks arising from the activities of the corporate purpose. In this regard, compliance can be interpreted as an auxiliary instrument, which helps management achieve a company’s goals, by providing relatively safe standards of action. In this way, the law manifests itself as a guide that serves to channel the economic activity of a company. However, regulations also operate as a standard that allows an expost evaluation on the conformance of business management. The existence of norms that set a previous course of safe action implies risks for those who choose not to exercise the duty of surveillance. Thus, the administration must combine a careful observation of norms, with the exercise of economic freedom, in order to implement a safe but productive business activity.